Epithelioid hemangioendotheliomas of the liver and lung in children and adolescents. Issue 12 (9th June 2017) - Hettmer, Simone; Andrieux, Geoffroy; Hochrein, Jochen; Kurz, Philipp; Rössler, Jochen; Lassmann, Silke; Werner, Martin; von Bubnoff, Nikolas; Peters, Christoph; Koscielniak, Ewa; Sparber‐Sauer, Monika; Niemeyer, Charlotte; et al.
Abstract: Epithelioid hemangioendothelioma (EHE) is a rare, vascular sarcoma. Visceral forms arise in the liver/ lungs. We review the clinical and molecular phenotype of pediatric visceral EHE based on the case of a 9‐year‐old male child with EHE of the liver/lungs. His tumor expressed the EHE‐specific fusion oncogene WWTR1‐CAMTA1 . Molecular characterization revealed a low somatic mutation rate and activated interferon signaling, angiogenesis regulation, and blood vessel remodeling. After polychemotherapy and resection of lung tumors, residual disease remained stable on oral lenalidomide. Literature review identified another 24 children with EHE of the liver/lungs. Most presented with multifocal, systemic disease. Only those who underwent complete resection achieved complete remission. Four children experienced rapid progression and died. In six children, disease remained stable for years without therapy. Two patients died from progressive EHE 21 and 24 years after first diagnosis. Natural evolution of pediatric visceral EHE is variable, and long‐term prognosis remains unclear.